Full-Scale Tests of Pipeline Girth Welds Under Complex Cyclic Internal Pressure and Static Bending Loading Conditions - Dakhel, Ahmad Yasser; Lukács, János (International Journal of Engineering and Management Sciences, 2023)
The critical elements of high-pressure hydrocarbon transporting pipelines are often the girth welds, which are subjected to complex loads. The aims of our research and this paper are to introduce our full-scale pipeline fatigue and burst tests applying cyclic internal pressure and superimposed external bending stress on girth welds, furthermore, attracting the importance and the applicability of the investigation results. A unique testing system was built to study the behaviour of pipeline girth welds under simultaneous loads. The tests were evaluated using video camera recordings, internal pressure vs. burst time functions and failure pressure values.